Quality of nursing care as perceived by cancer patients: a cross-sectional survey in four European countries - Adam, Christina; Patiraki, Elisabeth; Lemonidou, Chryssoula; Radwin, Laurel E.; Charalambous, Andreas; Charalambous, Melanie; Berg, Agneta C.; Sjövall, Katarina; Katajisto, Jouko K.; Stolt, Minna; Suhonen, Riitta A. (My University, 2017)
Purpose: To explore and compare cancer patients' perceptions on the quality of nursing care in four European countries. Methods: Data were collected in Cyprus, Finland, Greece and Sweden. The sample comprised 596 hospitalized cancer patients. The quality of nursing care was measured using the “Oncology Patients' Perceptions of the Quality of Nursing Care Scale” (OPPQNCS). Patient characteristics were also collected. Analysis of variance was used to examine the effects of country on the perceptions of the quality of nursing care. Results: Patients' age ranged from 18 to 86 years, and 58% were male. The comparison of cancer patients' perceptions regarding the quality of nursing care between the four countries showed a statistically significant difference in the total OPPQNCS scores (p<0.001) as well as in the subscales responsiveness (p<0.001), individualization (p<0.001), coordination (p<0.001) and proficiency (p<0.001). The Cronbach's alpha coefficient for the OPPQNCS ranged between 0.89 and 0.95. A multivariate analysis of variance for the OPPQNCS controlled by respondents' demographic characteristics revealed that only the patient's country was significantly related with the patients' perceptions of quality care. Conclusion: Quality of nursing care as perceived by cancer patients was high, but differed between the four countries. The impact of the clinical status of cancer patients on the quality of nursing care and managerial factors such as staffing/nursing care delivery models that influence the ability of nurses to offer high quality care should also be explored by more focused studies.
Keywords: Cross-country comparison; Oncology patients; Quality nursing care; Survey